Faktor Determinan Kejadian Covid-19 di Kecamatan Nanga Pinoh Kabupaten Melawi Tahun 2021 - Eka Hariani; A’ang Mardiata (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2). Common symptoms include fever, dry cough, fatigue, and in some more serious cases, shortness of breath and gastrointestinal disturbances. Based on WHO data (2021) globally, on October 3, 2021, the number of COVID-19 cases was 234,551,981 cases and the death rate was 4,796,171 cases. Based on data from the Health Office, Nanga Pinoh Subdistrict is the highest number of Covid-19 cases, with 1,815 confirmed cases and 51 deaths. The purpose of the study was to determine the determinants of the incidence of Covid-19 in the District of Nanga Pinoh, Melawi Regency. This type of analytic observational research with a case control design with a ratio of 1:1. The sample in this study were 96 cases and 96 controls taken through total sampling technique. The test used is the chi-square test. The results of statistical tests showed that there was a significant relationship between health protocols (p value = 0.043; OR = 0.531), knowledge (p value = 0.017; OR = 0.467), attitudes (p value = 0.013; OR = 0.457) and there was no relationship between the role of health workers (p value = 0.663; OR = 0.845) and the incidence of Covid-19 in Nanga Pinoh District, Melawi Regency. It is recommended to improve health services in an effort to prevent and transmit the spread of the Covid-19 disease.